Electrospinning of annatto-loaded cellulose acetate scaffolds using acetone/DMSO as solvent - Dreier Tim; Neukirch Florian; Priebe Hannes; Seitz Hermann (Current Directions in Biomedical Engineering, 2024)
Electrospinning has emerged as a versatile technique for producing nanofibers for diverse applications. The fibers produced are highly regarded for their biocompatibility, exceptional surface-to-volume ratios, porosity, and adjustable composition properties, making them promising scaffolds for tissue engineering. In the literature, annatto-loaded cellulose acetate has already been successfully used for electrospinning. However, N,N-dimethylformamide (DMF) was utilized as a solvent in the experiments, which is considered a carcinogenic and mutagenic substance. The aim of this study is to analyze whether comparable results can be achieved with a low toxicity solvent consisting of acetone and dimethyl sulfoxide (DMSO). In this study, we investigate the electrospinning process of cellulose acetate (CA) and cellulose acetate combined with annatto extract (CA/A). Initially, various polymer concentrations ranging from 12% to 16% (w/v) were characterized by rheological measurements to determine their suitability for electrospinning. The morphology and diameter distribution of the electrospun fibers were analyzed using scanning electron microscopy (SEM). Contact angle measurements were carried out to determine the wettability of the electrospun meshes. The rheological investigations conducted revealed that increasing the polymer content of CA raises viscosity, while the incorporation of annatto decreases it. Uniform fibers are achieved at polymer concentrations of 14% and above. The electrospun nanofibers exhibit uniform morphology and diameters in the nanometer range, indicating the successful fabrication of annatto-loaded CA nanofibers. The contact angle measurements showed hydrophilic behavior on all investigated meshes. The incorporation of annatto extract in the electrospun fibers holds promise for various applications, including biomedical scaffolds, scaffolds for cultured meat, filtration membranes and food packaging materials. This study provides valuable insights into optimizing electrospinning parameters for the fabrication of functional nanofibers with enhanced properties.